Combined transcriptomic and metabolomic analysis revealed that pH changes affected the expression of carbohydrate and ribosome biogenesis-related genes in Aspergillus niger SICU-33 - Zhang, Runji; Chen, Yulan; Wang, Wenxian; Chen, Juan; Liu, Dongyang; Zhang, Lingzi; Xiang, Quanju; Zhao, Ke; Ma, Menggen; Yu, Xiumei; Chen, Qiang; Penttinen, Petri; et al. (Frontiers in Microbiology, 2024)
The process of carbohydrate metabolism and genetic information transfer is an important part of the study on the effects of external environment on microbial growth and development. As one of the most important environmental parameters, pH has an important effect on mycelial growth. In this study, the effects of environmental pH on the growth and nutrient composition of Aspergillus niger (A. niger) filaments were determined. The pH values of the medium were 5.0, 7.0 and 9.0, respectively, and the molecular mechanism was further investigated by transcriptomics and metabolomics methods. The results showed that pH 5.0 and 9.0 significantly inhibited filament growth and polysaccharide accumulation of A. niger. The results showed that the mycelium biomass of A. niger and the crude polysaccharide content was higher when the medium pH 7.0, and the DEGs related to ribosome biogenesis were the most abundant, and the down-regulated expression of genes encoding XRN1, RRM, and RIO1 affected protein translation, modification, and carbohydrate metabolism in fungi. The dynamic changes of pargyline and choline were in response to the oxidative metabolism of A.niger SICU-33. The ribophorin_I enzymes and DL-lactate may be important substances related to pH changes during carbohydrate metabolism of A.niger SICU-33. The results of this study provide useful transcriptomic and metabolomic information for further analyzing the bioinformatic characteristics of A. niger and improving the application in ecological agricultural fermentation.